Integrating Tradition and Technology: A Multimodal Approach to Indonesian Arts and Culture Education for Diaspora Youth in Malaysia - Marsudi; Ratyaningrum, Fera; Suryandoko, Welly; Angge, Indah Chrysanti; Suwahyono, Agus (Proceeding of International Joint Conference on UNESA, 2025)
This qualitative case study aims to review the multidisciplinary framework and culture training program for the Indonesian diaspora at Sanggar Muallim in Malaysia. During the 6-month training program, documents for trainers and participants, as well as interviews with participants, teachers, and guests, were collated. Three components of the program were found to be interlinked. First is Education on the Arts and Culture of the Home Country and Local Wisdom Practised in Copper Metal Crafting and Folk Dance of Dolanan. Second is the Integration of Islamic Arts with Digital Augmented Reality (AR) Qasidah Cards and Apps and Teaching and Learning Islam. Third is the Development of Soft Skills: Communication, Collaboration, Creativity, and Mental Toughness. The program aims to address problems of relevance, balance, and culturally relevant, digitally accessible cultural heritage, an asset to the youth in the diaspora of the Indonesian nation. It also displays the living, inclusive Indonesian identity in the diaspora, enriched by 21st-century soft skills. This study supports the distribution of the curriculum design and documentation for the program and the initiation of longitudinal studies related to the curriculum